2019
DOI: 10.5430/cns.v7n2p71
|View full text |Cite
|
Sign up to set email alerts
|

Professional values of nursing students in nursing leadership and management course

Abstract: Introduction: Determining the innate professional values of nursing students during their academic years in nursing schools provide a more concrete measurement of their professional readiness when they become licensed nurses. Background: Among all nursing subjects and courses, the Nursing Leadership and Management contains topics that emphasize professional adjustment and value development among students to become more professionally ready for the real world experience of the nursing profession. Objective: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(32 reference statements)
1
0
1
Order By: Relevance
“…Variables Mean Differences With Nurses Professional Values Scale-3 , from Saudi Arabia;Sharif et al, 2018, from Pakistan) but lower than students in other studies (e.g.,Chisholm-Ford et al, 2016, from Jamaica;Leners et al, 2006;Weis & Schank, 2000, from the United States). ForAlboliteeh (2019), the caring subscale mean score was 3.37, activism was 3.28, and professionalism was 3.21, lower than this study; however, in Iran,Poorchangizi et al (2019b) reported mean scores as follows: caring, 3.85; activism, 3.61; and professionalism, 3.47. In the United States, Fisher (2014) reported a caring subscale score of 4.2, andLeners et al (…”
contrasting
confidence: 88%
See 1 more Smart Citation
“…Variables Mean Differences With Nurses Professional Values Scale-3 , from Saudi Arabia;Sharif et al, 2018, from Pakistan) but lower than students in other studies (e.g.,Chisholm-Ford et al, 2016, from Jamaica;Leners et al, 2006;Weis & Schank, 2000, from the United States). ForAlboliteeh (2019), the caring subscale mean score was 3.37, activism was 3.28, and professionalism was 3.21, lower than this study; however, in Iran,Poorchangizi et al (2019b) reported mean scores as follows: caring, 3.85; activism, 3.61; and professionalism, 3.47. In the United States, Fisher (2014) reported a caring subscale score of 4.2, andLeners et al (…”
contrasting
confidence: 88%
“…Male students scored higher on the caring subscale, as did employed students, bridging students, and those studying in private universities. Nursing students in our study scored similarly or higher than students in some previous studies (e.g., Alboliteeh, 2019, from Saudi Arabia; Sharif et al, 2018, from Pakistan) but lower than students in other studies (e.g., Chisholm-Ford et al, 2016, from Jamaica; Leners et al, 2006; Weis & Schank, 2000, from the United States). For Alboliteeh (2019), the caring subscale mean score was 3.37, activism was 3.28, and professionalism was 3.21, lower than this study; however, in Iran, Poorchangizi et al (2019b) reported mean scores as follows: caring, 3.85; activism, 3.61; and professionalism, 3.47.…”
Section: Discussionsupporting
confidence: 49%